A case study of rice blast disease at Pertubuhan Peladang Kawasan (PPK) Sungai Besar, Selangor / Muhamad Nasarudin Sulaiman - Sulaiman, Muhamad Nasarudin (Faculty of Plantation and Agrotechnology, 2017)
The part of agenda in food security that has been addressed in the World Food Summit 1996 is produce more rice than it does due global demand increase from years to years. Meanwhile in Malaysia, rice is staple food for Malaysians and source of income for farmers. Unfortunately, there are several major diseases in paddy cultivation that give impact for rice production. Rice blast disease caused by Pyricularia oryzae seems to be harmed to the rice crops at PPK Sungai Besar, Selangor. Currently, paddy cultivation in Sungai Besar, Selangor are having slight disease problem especially rice blast disease which effect their production. Therefore, several areas in Sungai Besar’s PPK were studied during early August 2016. The objectives are to determine the incidence and severity of blast disease in severe granary areas at PPK Sungai Besar, Selangor and to relate the factors that affecting incidence and severity of blast disease at the area surveyed. A survey has been carried out at three field plot. A pipe 1m x 1m was used to measure placed randomly on the five quadrant. All the data were recorded. Result indicated that from three fields that have been surveyed, Field C has the highest mean of disease incidence with 49.20% whereas severity is 52.89%, followed by mean of disease incidence is Field B with 37.23% whereas severity is 41.33%. The lowest mean of disease incidence is Field A with 31.07% whereas severity is 25.33%. These disease incidence and severity were affected by several factors which were amount of fertilizer, amount of fungicide, soil pH, planting method, rice variety and climatic condition. As a conclusion, at PPK Sungai Besar, Selangor, disease incidence and severity on rice blast disease is not in severe state.